ANALISIS BALANCED SCORECARD SEBAGAI PENGUKURAN KINERJA PERUSAHAAN MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA TAHUN 2020-2024 - Dyah Shinta Kusumaningtyas; Novita Eka Nuragustin; Joelianti Dwi Supraptiningsih (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2025)
This research analyzes the performance of nine food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2020-2024 using the Balanced Scorecard (BSC) approach, which includes financial aspects, customers, internal business processes, and growth and learning. The method used is descriptive quantitative with secondary data from financial and annual reports. The results showed that most of the companies experienced stable revenue growth, but still faced constraints in efficiency and liquidity. In terms of customers, Indofood CBP Sukses Makmur and Mayora Indah were able to maintain consumer loyalty, while others were affected by competition. In the internal process perspective, Campina Ice Cream Industry and Diamond Food Indonesia showed improvement, although not yet consistent. In the aspect of growth and learning, innovation and employee development have not been evenly distributed. This research emphasizes the importance of balance between perspectives to support long-term performance and competitiveness of the company.